Initial Outcomes of Provider-Initiated Routine HIV Testing and Counseling During Outpatient Care at a Rural Ugandan Hospital: Risky Sexual Behavior, Partner HIV Testing, Disclosure, and HIV Care Seeking - Kiene, Susan M. (Mary Ann Liebert, Inc., 2010)
Provider-initiated routine HIV testing is being scaled up throughout the world, however, little is known about the outcomes of routine HIV testing on subsequent behavior. This study examined the initial outcomes of provider-initiated routine HIV testing at a rural Ugandan hospital regarding partner HIV testing, sexual risk behavior, disclosure, and HIV care seeking. In a prospective cohort study, 245 outpatients receiving routine HIV testing completed baseline and 3-month follow-up interviews. After receiving routine HIV testing the percentage of participants engaging in risky sex decreased from 70.1% to 50.3% among HIV-negative and from 75.0% to 53.5% among HIV-positive participants, the percentage knowing their partner(s)’ HIV status increased from 18.7% to 34.3% of HIV-negative and from 14.3% to 35.7% of HIV-positive participants. Among those reporting risky sex at baseline, HIV-positive participants were more likely to eliminate risky sex in general and specifically to become abstinent at follow-up than were HIV-negative participants. Similarly, unmarried participants who were risky at baseline were more likely to become safe in general, become abstinent, and start 100% condom use than were married/cohabitating participants. Rates of disclosure were high. Over 85% of those who tested HIV positive enrolled in care. Routine HIV testing in this setting may promote earlier HIV diagnosis and access to care but leads to only modest reductions in risky sexual behavior. To fully realize the potential HIV prevention benefits of routine HIV testing an emphasis on tailored risk-reduction counseling may be necessary.